Analisis Sistem Pelayanan Pasien Rawat Inap Pengguna Jaminan Persalinan (Jampersal) di RSUD Abdul Aziz Singkawang - Diana Barsasella; Ibnu Safari (Jurnal Persada Husada Indonesia, 2014)
Health is very important in life and also very expensive. In theera of globalization, many people hasbegun to increase their awareness in order to stay healthy at the direction of the Health Act 2009. One of themeasures taken by the government in financing health care is to establish health insurance through Maternity Insurance (Jampersal). The purpose of this study is to identify the inpatient care system with Jampersal (Jaminan Persalinan). This research uses a descriptive qualitative approach that obtained from in-depth interviews, observation and documentations studies. Number of respondents are six people. The results shows that the services for inpatient’s health care is still not optimal due to interrelated factors but health care coverage has been well-characterized by the number of patients. The results suggested the need to improve services related to a variety of factors, including the human resources, facilities, and procedures.